2016
DOI: 10.1177/1524838016683460
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Victim Credibility in Child Sexual Assault Cases: A Systematic Review

Abstract: While the concept of credibility seems like an intuitive one, research has indicated that there is no consistent definition of this construct and that credibility may, in fact, be multidimensional. This article is the first to review how the measurement of credibility in child sexual assault cases has been conducted, with the view to improve how credibility is psychometrically measured. Our findings indicate that the majority of experiments have been conducted in the United States (67%), have been based primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
(79 reference statements)
1
3
0
1
Order By: Relevance
“…Few measures included items about the accuracy of the complainant’s testimony and no measures contained items about the reliability of the complainant’s evidence. This matches a recent review of credibility measures for child sexual abuse complainants, which found that items about accuracy and reliability were rarely used (Voogt, Klettke, & Crossman, 2016). This omission is problematic as jurors are typically directed to consider the complainant’s reliability related to credibility (e.g., in Australia and Canada; McKimmie et al, 2014; Porter & ten Brinke, 2009; White v R , 1947).…”
Section: Discussionsupporting
confidence: 85%
“…Few measures included items about the accuracy of the complainant’s testimony and no measures contained items about the reliability of the complainant’s evidence. This matches a recent review of credibility measures for child sexual abuse complainants, which found that items about accuracy and reliability were rarely used (Voogt, Klettke, & Crossman, 2016). This omission is problematic as jurors are typically directed to consider the complainant’s reliability related to credibility (e.g., in Australia and Canada; McKimmie et al, 2014; Porter & ten Brinke, 2009; White v R , 1947).…”
Section: Discussionsupporting
confidence: 85%
“…Informed by past research (Savage et al, 2017; Voogt et al, 2019), perceptions of victim credibility were assessed using six items that asked participants how much they agreed or disagreed with the statements on a 7-point Likert type scale ranging from 1 ( Strongly Disagree ) to 7 ( Strongly Agree ). Sample items included: “The alleged victim was credible,” and “The alleged victim was believable.” All six items were summed and averaged to create an individual rating ( M = 4.83, SD = .93), where higher ratings were associated with perceptions of the victim being more credible.…”
Section: Methodsmentioning
confidence: 99%
“…Informed by past research (Savage et al, 2017;Voogt et al, 2019), perceptions of victim credibility were assessed using six items that asked participants how much they agreed or disagreed with the statements on a 7-point Likert type scale ranging from 1 (Strongly Disagree) to 7 (Strongly Agree). Sample items included: "The alleged victim was credible," and "The alleged victim was believable."…”
Section: Victim Credibilitymentioning
confidence: 99%
“…A potential reporter’s confidence in ability to assess if a formal report is warranted is also likely to be influenced by judgments of the child’s credibility, particularly in cases in which the child has verbally described abuse. Credibility evaluations are pervasive in children’s process through social services and justice systems: Often, the only evidence supporting a child’s claim of abuse is their statement (e.g., Voogt et al, 2019 ). Children’s credibility has been conceptualized as falling along two dimensions: honesty and cognitive competence ( Ross et al., 2003 ).…”
Section: Reporting Decisionsmentioning
confidence: 99%